Penerapan Metode Sariswara untuk Meningkatkan Hasil Belajar Matematika pada Siswa Kelas III SD - Sakinah, A’yun Nur; Trisniawati, Trisniawati; Rhosyida, Nelly (Piramida Akademi, 2023)
The purpose of this study is to describe the application of the sariswara method to enhance mathematics learning objectives for the third class students at public elementary school 3 Taskombang Klaten. Classroom action research is the term for this kind of study. The study’s subjects were class III pupils at public elementary school 3 Taskombang, consisting of 31 students. This research was used in II cycles, in each cycle two meetings were held. Methods of gathering data use observation, examination, documentation additionally giving questionnaires. The data interpretation technique utilized is both numerical and descriptive descriptive to analyze learning objectives. The outcomes of this research show that using the sariswara technique can get better mathematics learning objectives for class III pupils at SD Negeri 3 Taskombang. This can be seen based on the mean value of students' mathematics learning objectives for cycle I, cycle II and pre-cycle. The increase that occurred was the average pre-cycle score of 48 with a KKM achievement percentage of 9.6%. After applying the sariswara method, the average value for cycle I increased, namely 63.32 with a KKM achievement percentage of 48.38%, while the average value for cycle II was 84.48 with a KKM achievement percentage of 87.09%. This demonstrates a rise between cycle I and cycle II. The implications of education using the sariswara method make students more interested and their enthusiasm for learning increases and improves student learning objectives.